1995
DOI: 10.1002/dev.420280603
|View full text |Cite
|
Sign up to set email alerts
|

Prenatal stress alters immune function in the offspring of rats

Abstract: Pregnant rats were either exposed to restraint under bright lights for 45 min three times daily (n = 7) or were left undisturbed (n = 8) during Days 14-21 of gestation. Offspring were tested for cellular immune responses as measured by Concanavalin A-stimulated proliferation and Natural Killer (NK) cytotoxicity of splenocytes as juveniles or adults, or were tested for specific humoral immune responses to in vivo challenge with the antigen Keyhole Limpet Hemocyanin (KLH) as adults. Results indicated that: (a) P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
34
0
1

Year Published

2001
2001
2014
2014

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 74 publications
(36 citation statements)
references
References 54 publications
1
34
0
1
Order By: Relevance
“…Other studies showed only a decrease in the CD8ϩ subsets (26) or a gender difference in splenocyte response to mitogens, but no difference in the T-lymphocyte subsets (30). Prenatal stress is also associated with an altered response to stimulation with LPS (28) or the potent mitogen concanavalin A (27,29). The wide spectrum of results seen in these studies is likely a function of the model variance in type, onset, and duration of stress.…”
Section: Discussionmentioning
confidence: 73%
See 1 more Smart Citation
“…Other studies showed only a decrease in the CD8ϩ subsets (26) or a gender difference in splenocyte response to mitogens, but no difference in the T-lymphocyte subsets (30). Prenatal stress is also associated with an altered response to stimulation with LPS (28) or the potent mitogen concanavalin A (27,29). The wide spectrum of results seen in these studies is likely a function of the model variance in type, onset, and duration of stress.…”
Section: Discussionmentioning
confidence: 73%
“…These models include repeated stimulation of maternal rats to confrontation (25), acute immobilization (26), bright light (27,28), and loud noise (29,30). These studies have shown a decrease in total peripheral leukocyte count (26,31) and decreases in the peripheral CD4ϩ and CD8ϩ T-cell subsets in older rats (31).…”
Section: Discussionmentioning
confidence: 99%
“…Exposure of pregnant dams to footshock stress, psychological stress, and noise stress has all been shown to alter IgG levels in juvenile rats (19), and prenatal noise stress exposure has also been shown to reduce arthus skin reactions and delayed-type hypersensitivity reactions in offspring. Adult rat offspring of prenatally stressed dams also exhibit increased antibody response to antigen, although prenatal stress effects are less marked for natural killer (NK) cell cytotoxicity and are not observed for splenocyte proliferative responses to mitogens (20). These data are further confirmed by observations of Kay et al (21) that prenatal stress exposure reduces NK cell cytotoxicity in both the spleen and the blood but that these effects are less pronounced for splenocyte responses to phytohemagglutinin.…”
Section: Prenatal Maternal Influencesmentioning
confidence: 64%
“…Previous research involving prenatal manipulation and immune function in the offspring has focused on the effects of environmental toxins, dietary alterations and various pharmaceuticals (Silva et al 1968, Roberts & Chapman 1981, Schmidt 1984. Daily handling, anxiety, electric foot-shocks, restraint with or without bright lights and elevated temperatures, noise, crowding and other stressor stimuli applied to dams can cause these changes in their adult offspring (Ader & Plaut 1968, Fride & Weinstock 1984, 1989, Harvey & Chevins 1985, Sobrian 1988, VonSaal et al 1991, Sobrian et al 1992, Klein & Rager 1995, Silva & Palermo-Neto 1999, Williams et al 1999a. In contrast, power frequency alternating magnetic fields had no effect on reproduction and prenatal development of mice (Yasuyuki et al 2002).…”
mentioning
confidence: 99%